Sosialisasi Santunan Penjaminan PT. Jasa Raharja Akibat Kecelakaan Lalu Lintas - Nurhakim, Rahman; Saefullah, Aep; Fahri, Fahri; Arza, Zubair; Firdaus, Adhy; Noor, , M. Arief; Tjiwidjaja, Halim; Hidayatullah, Syarif (Journal of Community Research & Engagement, 2024)
Driving activities on the highway are inseparable from various risks such as accidents and death. The government as the executor to protect the public makes some rules aimed at ensuring the implementation of accident insurance that occurs while driving. The government established PT Jasa Raharja to implement the rules that have been made, both in the form of Laws, Government Regulations or Minister of Finance Regulations. Information on traffic accident insurance is not known by all levels of society, both in terms of claim procedures, requirements and also types of accidents that can be covered, so that many people end up being burdened by the accidents that occur. STIE Ganesha conducts community service programs in collaboration with related parties to provide socialization about driving safety on the highway, including socialization about guarantees for traffic accident victims carried out by PT Jasa Raharja. The participants who were targeted in this socialization were students, offline motorcycle taxi drivers, surrounding communities and also STIE Ganesha employees. This service went well so that the participants could understand the material given during the event and could become a liaison between the community and information about traffic accident guarantees.